2004
DOI: 10.1021/ac049058c
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Photoionization-Mass Spectrometry with a Microchip Heated Nebulizer

Abstract: A novel, microfabricated heated nebulizer chip for atmospheric pressure photoionization-mass spectrometry (APPI-MS) is presented. The chip consists of fluidic and gas inlets, a mixer, and a nozzle etched onto silicon wafer that is anodically bonded to a Pyrex glass wafer, on which an aluminum heater is sputtered. A krypton discharge lamp is used as the source for 10-eV photons to initiate the photoionization process. Dopant, delivered as part of the sample solution, is used to achieve efficient ionization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Acidic species can deprotonate to form (M Ϫ H) Ϫ and positive electron affinity compounds can capture thermal electrons and form M -• . Kostiainen et al studied negative ion formation mechanisms by investigating ionization efficiency and ion type (even-or odd-electron ion) for analytes of different polarity in various solvents [3,7]. Traldi et al reported negative ion formation by resonant electron capture from thermal electrons originating from metal surfaces and dopant [8].…”
Section: And [M ϩ D]mentioning
confidence: 99%
“…Acidic species can deprotonate to form (M Ϫ H) Ϫ and positive electron affinity compounds can capture thermal electrons and form M -• . Kostiainen et al studied negative ion formation mechanisms by investigating ionization efficiency and ion type (even-or odd-electron ion) for analytes of different polarity in various solvents [3,7]. Traldi et al reported negative ion formation by resonant electron capture from thermal electrons originating from metal surfaces and dopant [8].…”
Section: And [M ϩ D]mentioning
confidence: 99%
“…Also, the flow rates applicable to current commercial APCI and APPI ion sources are high, typically 50-1,000 mL/min, thus excluding analysis with minimal sample volumes. For these reasons, a miniaturized heated nebulizer was developed for microchip-based APCI (Ö stman et al, 2004; Ö stman et al, 2006a,b) and APPI (Kauppila et al, 2004a). Later, the same microchip was used as a sonic spray (SSI) (Pol et al, 2007) or thermospray (TSI) ion source (Keski-Rahkonen et al, 2008).…”
Section: Miniaturized Heated Nebulizer For Chemical Photo- Supementioning
confidence: 99%
“…The thermal nebulizer chips incorporate fluidic inlets, a mixer, a heater, and a spraying nozzle so that only fluidic connectors needed to be manually assembled afterwards. The first prototype of the chip was successfully applied to the ionization of small molecules by APCI (Ö stman et al, 2004) and APPI (Kauppila et al, 2004a).…”
Section: Miniaturized Heated Nebulizer For Chemical Photo- Supementioning
confidence: 99%
See 1 more Smart Citation
“…In mass spectrometry, the majority of the effort has been put to miniaturization of ion sources, especially electrospray ionization (ESI) [4]. However, other miniaturized ion sources, e.g., the heated nebulizer microchip for atmospheric pressure chemical ionization ( APCI) [5] and atmospheric pressure photoionization ( APPI) [6], and the nebulizer microchip for sonic spray ionization (SSI) [7], have been reported as well. The heated nebulizer microchips can be used to connect a capillary liquid chromatograph (cap LC) [8,9] or a gas chromatograph (GC) [9 -11], with any mass spectrometer with an atmospheric pressure ionization (API) source, or as a heated sprayer in desorption atmospheric pressure photoionization [12].…”
mentioning
confidence: 99%